Effect of Processing on Antinutrient Compounds in Pulses. Issue 1 (11th October 2016) - Patterson, Carol Ann; Curran, Julianne; Der, Tanya
Abstract : Processing of pulses (peas, beans, lentils, chickpeas, and faba beans) is necessary to reduce or eliminate the antinutrient compounds. Conventional processing including soaking, dehulling, boiling, and pressure cooking as well as germination and fermentation reduce the levels of phytate, protease inhibitors, phenolics, condensed tannins, lectins, and saponins. Recent research has investigated how innovative processes such as extrusion, microwave heating, micronization, and irradiation affect the antinutrient content. Germination tends to be most effective at reducing phytate levels, regardless of pulse type. Mixed results on the effectiveness of extrusion, microwave heating, and micronization have been reported. More work is needed to understand how processing of consumer‐ready foods containing pulse ingredients affects levels of antinutrient compounds.